Women and men, authors and victims of workplace bullying in Italy: a literature review - Dassisti, Liliana; Stufano, Angela; Lovreglio, Piero; Vimercati, Luigi; Loconsole, Pasqua; Grattagliano, Ignazio (La Medicina del Lavoro, 2020)
Introduction: It is known in literature that women are frequently victims of murder, sexual assault and stalking. It is interesting to investigate the gender characterization when workplace bullying occurs. Objectives: To investigate the phenomenon of workplace bullying and to understand if there are any relevant data about the gender aspects of workplace bullying by reviewing the literature in Italy. Methods: Review of articles on a sample of Italian workers. The research question followed the P.E.C.O. model and the article selection is based on PRISMA statement. Fourteen research strings were applied on: Pubmed, Microsoft Academic e Science Direct. A total of 32 articles were selected. Results: There are few studies in which gender differences on workplace bullying and crimes related are analysed, in some cases it is considered in the research but not in the results section (n=6 articles). In the studies selected women are predominantly victims (n=10 articles), the aggressors instead are usually men (n=2 articles). The attacks suffered by women are frequently discriminations due to family management, children and gender related issues (n=6 articles). Men have the major consequences on mental health if compared to women (n=7 articles). Conclusions: Gender is relevant in the characterization of workplace bullying. There is a need for further investigation focusing on gender differences between perpetrators and victims of workplace bullying offences. A unique evaluation protocol is necessary for evaluating workplace bullying, the crimes linked to it and gender differences, to obtain a more accurate comparability of data.